VARIASI DAN RELASI SEMANTIS LEKSIKAL BAHASA SUNDA LULUGU: ANALISIS DIAKRONIS DATA LINGUAL (LULUGU’S VARIATIONS AND LEXICAL SEMANTIC RELATIONSHIPS LULUGU: DIACHRONIC ANALYSIS OF LINGUAL DATA) - Winci Firdaus; Asri Hafsari (Kadera Bahasa, 2018)
The meaning of a lexem or word diacronically can change. The change of meaning in a language occurs with the passage of time. Similarly, the change of meaning that occurs in Sundanese. The research describes change of lexical meaning in Lulugu Sundanese (bahasa Sunda Lulugu; BSL) from old Sundanese (bahasa Sunda Kuno; BSK). The purpose of this research is to see the change of meaning in Sundanese Lulugu. The method used in this research is descriptif comparative method with range time diachronic. From the results of the analysis can be concluded the change of meaning in the form of extention-ristriction meaning, total change of meaning, euphemism, disphemism, and connotation change.